Phenolic profile, alpha-amylase inhibitory activity, and in vitro glycemic index of adzuki beans - Muhammad, Mazhar; Zhu, Yong; Wen, Anyan; Liu, Na; Qin, Likang (Frontiers in Nutrition, 2022)
Regular consumption of low-glycemic index (GI) foods is a common strategy for type 2 diabetes patients. To evaluate the potential application of adzuki beans in low-GI foods, the phenolic profile and alpha-amylase inhibitor (α-AI) activity of four varieties of adzuki beans (G24, Te Xiao Li No.1, Gui Nong No.1, and Qian Xiao Hei) were determined. The starch digestibility properties and in vitro glycemic index (IVGI) of these beans were also evaluated using the in vitro digestion model coupled with 3,5-dinitrosalicylic acid colorimetry. The results indicated that these adzuki beans, containing numerous phenolics, showed inhibitory activities to alpha-amylase with the α-AI activities between 1.760 ± 0.044 and 3.411 ± 0.186 U/g. The resistant starch contributed predominantly to the total starch with proportions between (69.78 ± 2.45%) and (81.03 ± 0.06%); Te Xiao Li No.1 was the highest compared with the other varieties. The adzuki beans were categorized into low- or medium-GI foods, and the IVGI ranged from (39.00 ± 0.36) to (56.76 ± 4.21). These results suggested that adzuki beans can be used as a component of low-GI foods.